Efficacy of aid projects - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
When aid is no help John Madeley 1990 132pp UKL8.95 ISBN 85339 077 1 Intermediate Technology Publications, 103/105 Southampton Row London WC1B 4HH, UK